Evaluating SinergiAPS, an intervention based on patient feedback to improve patient safety in primary care: a cluster randomized trial - Maria Antònia Fiol-deRoque; José María Valderas; María Jesús Serrano-Ripoll; Montserrat Gens-Barbarà; Francisco Martín-Luján; Encarna Sánchez-Freire; Juan José Montaño; Sofía Mira-Martínez; Guadalupe Pastor-Moreno; Rocío Zamanillo-Campos; Pau Riera-Serra; Ignacio Ricci-Cabello (BMC Medicine)
Abstract Background Patient safety, defined by the WHO as the absence of preventable harm, is a critical component of healthcare quality and poses a significant challenge globally. This study aimed to evaluate the effectiveness of SinergiAPS, a patient-centred audit and feedback intervention, in improving patient safety in primary healthcare (PHC) centres. Methods We conducted a 12-month cluster randomized controlled, multicentre trial. Fifty-nine PHC centres (1053 PHC professionals) in Spain were recruited and randomly allocated (1:1) to usual care or SinergiAPS intervention. The SinergiAPS intervention comprised: a bespoke feedback report with results from audits of patient safety based on the Patient Reported Experiences and Outcomes of Safety in Primary Care (PREOS-PC) questionnaire, administered to 75 patients/centre; a set of educational materials, and a structured template to record safety improvement plans. The primary outcome (at the PHC professional level) was patient safety culture (Medical Office Survey on Patient Safety Culture (MOSPSC) questionnaire). Secondary outcomes (at the centre level) were patient-reported safety (six PREOS-PC scales), and rate of avoidable hospital admissions. After a 12-month follow-up, we conducted 15 semi-structured interviews with PHC professionals to explore their perceptions of the intervention. Results During the 12-month follow-up, 10 of the 30 centres in the intervention group held action plan team meetings and eight registered 57 safety improvement action plans. The plans aimed to improve patient activation, address treatment-related incidents, enhance communication between patients and providers, and strengthen patient safety culture. At 12 months, no significant differences were observed in MOSPSC mean score (intervention: 3.60 [95% CI 3.55 to 3.64] vs. control: 3.64 [3.60 to 3.68]). Similarly, no differences were observed in the secondary outcomes, with both groups experiencing a decline in patient-reported safety and avoidable hospital admissions. The qualitative interviews evidenced that the onset of the COVID-19 pandemic 6–9 weeks after initiating the follow-up period severely limited PHC’s capacity of developing and implementing safety improvement action plans, despite high levels of acceptability and perceived utility of the SinergiAPS intervention. Conclusions In the context of the health emergency caused by the COVID-19 pandemic, SinergiAPS did not improve patient safety in Spanish PHC centres. Trial registration ClinicalTrials.gov (NCT03837912).